Disinfection Performance in Wastewater Stabilization Ponds in Cold Climate Conditions: A Case Study in Nunavut, Canada - Lei Liu; Alan MacDougall; Geof Hall; Pascale Champagne (Environments, 2017)
Disinfection processes in passive wastewater treatment systems, which are dependent on natural purification, can be greatly influenced by environmental factors. In the Canadian Arctic, the passive systems face more challenges due to the extreme environmental conditions. The new Wastewater Systems Effluent Regulations (WSER) were implemented in Canada in 2012. Currently, they do not apply in the far North due to the limited wastewater treatment infrastructure in northern communities. In the summer of 2015, a field investigation was conducted to Pond Inlet, Nunavut, to assess the pathogen removal and inactivation of a wastewater stabilization pond (WSP). Sunlight disinfection was considered only effective at the water surface. The system achieved 0.76–1.2 log removal of E. coli and 0.79–1.02 log removal of total coliforms during the treatment season in 2015. Prior to annual decant, the average concentration of E. coli was 1.3 × 106 CFU/100 mL in the WSP, which exceeded discharge guidelines of 104 to 106 CFU/100 mL set by the Nunavut Water Board (NWB). Existing WSP disinfection models, which were typically designed for temperate or tropical regions, were selected to study their viability to predict the pathogen removal of Arctic WSPs. In general, the models over-predicted disinfection performance by an order of magnitude or more, and some were unable to replicate trends in the data. A modified model for northern WSPs should be developed in order to accurately predict disinfection performance.